Universal access to genetic counseling for women with epithelial ovarian cancer in Nova Scotia: Evaluating a new collaborative care model. Issue 5 (19th April 2021) - Warias, Ashley; Ferguson, Meghan; Chamberlain, Erin; Currie, Lauren; Snow, Nicole; Matheson, Kara; Penney, Lynette S.; Kieser, Katharina
Abstract: Women with pathogenic variants in BRCA1/2 have a significantly increased lifetime risk of breast and ovarian cancers. The availability of genetic testing to identify BRCA1/2 carriers is imperative to disease prevention and treatment. We evaluated the effectiveness of a new collaborative care model in Nova Scotia, involving the integration of genetic counselors into tumor board rounds, reduction in time allotted for initial genetic counseling appointments from 60 to 45 min, and a standardized dictation template, to increase referral rate for genetic counseling. We also assessed the study cohorts' preferences on timing for genetic testing. A retrospective chart review was performed on all women diagnosed with epithelial ovarian cancer (EOC) from 2012 to 2017 ( N = 386). Pertinent clinical outcomes were categorized and wait times to different nodes of the clinical pathway assessed. A questionnaire was sent to this same cohort of women to identify preference for the timing of genetic testing ( n = 103). The chi‐square and Wilcoxon's rank‐sum tests were used to compare demographic and clinical variables pre‐ and post‐care model implementation. We identified a 48.2% (95% CI: 39.4–56.7, p < .001) increase in referral for genetic counseling following implementation of the new care model. Median time from diagnosis to referral decreased by 74.0 days ( p < .001) and median time from referral to first appointment by 54.0 days ( p < .001). 56.3% of women desired referral at the time of diagnosis. This care model for women newly diagnosed with EOC in Nova Scotia was successful in increasing referral rates for genetic counseling. Majority of women pursued genetic testing following and favored that referral for genetic counseling be made at the time of diagnosis, highlighting the importance for timely access.